Arsenic Trioxide-Enhanced, Matrine-Induced Apoptosis in Multiple Myeloma Cell Lines - Yu, Qinghong; Chen, Binhai; Zhang, Xiang; Qian, WenBin; Ye, Baodong; Zhou, Yuhong (Planta Medica, 2013)
Matrine and arsenic trioxide are monomers used in traditional Chinese medicine possessing anti-myeloma activities. In this study, we evaluated the effects and mechanisms of matrine, arsenic trioxide, and their combination therapy on the proliferation and apoptosis of the myeloma cell lines RPMI8226 and U266. The effects of growth inhibition were measured by MTT, and apoptotic cells were analyzed by Hoechst 33258 staining and flow cytometry. The levels of caspase-3, poly (ADP-ribose) polymerase (a DNA repair enzyme), Bcl-2 and survivin (antiapoptotic signaling proteins), Bim (a proapoptotic signaling protein), total AKT, and phosphorylated AKT were evaluated by Western blot. Matrine significantly inhibited proliferation of RPMI8226 and U266 cell lines in a dose- and time-dependent manner with an IC50 at 24 h of 2.25 g/L and 2.18 g/L, and at 48 h of 1.64 g/L and 1.58 g/L, respectively. Arsenic trioxide also displayed a dose- and time-dependent inhibition of growth of multiple myeloma cell lines, and synergistic effects occurred when the two were combined. Matrine (0.5, 1.0 g/L) and arsenic trioxide (2, 4 ug/mL) induced the apoptosis of myeloma cells; more early-stage apoptotic cells were seen with the combination therapy (matrine 0.5 g/L plus arsenic trioxide 2 ug/mL and matrine 1.0 g/L plus arsenic trioxide 4 ug/mL). Activation of caspase-3 and poly (ADP-ribose) polymerase, upregulation of Bim expression, downregulation of Bcl-2, survivin expression, as well as inhibition of phosphorylated AKT related to matrine (0, 0.25, 0.5, 1.0, and 2.0 g/L)-mediated apoptosis, and the effects were enhanced when arsenic trioxide (8 ug/mL) was combined with matrine (1.0 g/L). In conclusion, matrine displayed anti-myeloma effects through apoptotic induction, and arsenic trioxide had synergistic effects with matrine enhancing matrine-induced apoptosis.
Keywords: matrine; arsenic trioxide; multiple myeloma; apoptosis